2008
DOI: 10.2174/156652408784533751
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Physical and Psychological Stress on the Gastrointestinal Tract: Lessons from Animal Models

Abstract: Physical and psychological stresses are widely accepted as triggers and / or modifiers of the clinical course of diverse gastrointestinal disorders such as peptic ulcer, irritable bowel syndrome or inflammatory bowel disease. Growing experimental evidence from a variety of models such as immobilization, thermal injury or early maternal deprivation in laboratory animals uniformly supports the ability of stress to induce the development of gastric ulcers, altered gastrointestinal motility and ion secretion, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 177 publications
(249 reference statements)
2
90
0
3
Order By: Relevance
“…Additionally, we observed that the PP subjects were more likely to be overweight (Table I) than their age-matched counterparts in the control group, although their body weights were not up to the standard of obesity. There is strong evidence that chronic life stress directly impacts gastrointestinal function in animals and humans (62)(63)(64) and increases the activity of both the hypothalamic-pituitary-adrenal axis and the sympathoadrenal system (65). As emerging evidence demonstrates the influence of gut microbiota on the development, behavior, and function of CNS (66), it is increasingly important to understand the intricate relationship between CNS, gut microbiota, and metabolic phenotypes in the development of precocious puberty.…”
Section: Urinary Metabolites From Triptorelin and Derivatives-trip-mentioning
confidence: 99%
“…Additionally, we observed that the PP subjects were more likely to be overweight (Table I) than their age-matched counterparts in the control group, although their body weights were not up to the standard of obesity. There is strong evidence that chronic life stress directly impacts gastrointestinal function in animals and humans (62)(63)(64) and increases the activity of both the hypothalamic-pituitary-adrenal axis and the sympathoadrenal system (65). As emerging evidence demonstrates the influence of gut microbiota on the development, behavior, and function of CNS (66), it is increasingly important to understand the intricate relationship between CNS, gut microbiota, and metabolic phenotypes in the development of precocious puberty.…”
Section: Urinary Metabolites From Triptorelin and Derivatives-trip-mentioning
confidence: 99%
“…A common finding observed in several models of stress-induced intestinal inflammation is an increased MPO activity in tissue homogenates (4). The tissue activity of this enzyme correlates linearly with neutrophil infiltration and has been widely used as a marker of acute inflammation (37).…”
Section: Effect Of Stress and Stroke On Bacterial Translocationmentioning
confidence: 99%
“…In fact, iNOS-derived nitric oxide (NO) has been shown to increase intestinal epithelial permeability both in vitro and in vivo (32,36). This effect seems to be related to NO-induced cytoskeleton rearrangement and subsequent TJ dysfunction (4,32). Furthermore, acute stress induces mast cell degranulation in the lamina propria as well as release of prostaglandins (4), and this process is downstream of COX-2 signaling.…”
Section: Ajp-regul Integr Comp Physiolmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all experimental-stress-inducing methods, those characterized by rodents exposed to an unavoidable, physical stress are the most extensively used. 18 In the present study, WIRS was employed to test the protective effect of the fruits of O. ficus indica var. saboten against stress-induced gastric lesions, since it is a widely used experimental model to induce acute stress ulcers in rats and is known for its reliable reproducibility.…”
Section: Discussionmentioning
confidence: 99%